Effect of distributed Bragg reflectors on photoluminescence properties of CH3NH3PbI3 film - Feng Jiang; Zhiguang Xiao; Mengqi Dong; Jiawen Song; Yinong Wang (Scientific Reports, 2022)
Abstract The nanoporous (NP) GaN distributed Bragg reflector (DBR) was prepared by using electrochemical etching. Then the NP-GaN DBR was pretreated by using ozone treatment. Atomic force microscopy and X-ray diffraction (XRD) were used to investigate the influence of ozone treatment on the structure of the substrates. The hybrid organic–inorganic CH3NH3PbI3 perovskite films were grown on the NP-GaN DBR and reference substrates by using a one-step solution method. The XRD and field emission scanning electron microscopy test results indicate the high quality of the prepared CH3NH3PbI3 perovskite films. The photoluminescence intensity of the prepared CH3NH3PbI3 perovskite film on the NP-GaN DBR substrate is ~ 3.5 times higher than that of the film on the reference substrate, with a 3.6 nm spectral blue-shift. The enhancement should be contributable to amplify spontaneous emission by resonant cavity, while the blue-shift could be contributable to stoichiometric difference of the films on different substrates.